2008
DOI: 10.1158/0008-5472.can-08-0667
|View full text |Cite
|
Sign up to set email alerts
|

LRRC3B, Encoding a Leucine-Rich Repeat-Containing Protein, Is a Putative Tumor Suppressor Gene in Gastric Cancer

Abstract: Leucine-rich repeat-containing 3B (LRRC3B) is an evolutionarily highly conserved leucine-rich repeat-containing protein, but its biological significance is unknown. Using restriction landmark genomic scanning and pyrosequencing, we found that the promoter region of LRRC3B was aberrantly methylated in gastric cancer. Gastric cancer cell lines displayed epigenetic silencing of LRRC3B, but treatment with the DNA methylation inhibitor 5-aza-2 ¶-deoxycytidine and/or the histone deacetylase inhibitor trichostatin A … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 43 publications
0
43
0
Order By: Relevance
“…LRRC3B has been reported to be a tumor suppressor for gastric cancer (24), and Tian et al (25) revealed the tumor suppressor role of LRRC3B in colorectal cancer using a gene silencing method. The role of LRRC3B in breast cancer has not been fully discussed, even in primary breast cancer surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LRRC3B has been reported to be a tumor suppressor for gastric cancer (24), and Tian et al (25) revealed the tumor suppressor role of LRRC3B in colorectal cancer using a gene silencing method. The role of LRRC3B in breast cancer has not been fully discussed, even in primary breast cancer surgery.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of studies have mentioned the pivotal role of LRRC3B in tumor development and progression. For instance, Kim et al (15) reported that LRRC3B was a tumor suppressor for gastric cancer. Furthermore, LRRC3B was downregulated in a renal cell carcinoma line, which suggests that LRRC3B could be involved in the process of carcinogenesis as a tumor suppressor (13,16).…”
Section: Introductionmentioning
confidence: 99%
“…Ninety-six paired frozen gastric tumor tissues and normal adjacent tissues were collected from the Tissue Bank at Chungnam National University Hospital. All samples were obtained with informed consent, and their use was approved by the institutional review board (19).…”
Section: Methodsmentioning
confidence: 99%
“…Anchorage-independent colony formation on these cell lines was determined as described previously [29] , with some modifications. Briefly, the cells were harvested and washed, and a total of 3×10 3 cells were resuspended in RPMI Medium 1640 containing 0.3% agarose.…”
Section: Soft Agar Assaymentioning
confidence: 99%